THE INFLUENCE OF GREEN PRODUCT AND DIGITAL MARKETING ON PURCHASING DECISIONS AT STARBUCKS CEMARA ASRI - Angga, Wellice; Dedy Lazuardi (PROCEEDING INTERNATIONAL BUSINESS AND ECONOMICS CONFERENCE (IBEC), 2024)
Technology is widely used by people to help their activities become more efficient. Without realizing it, their lifestyle has also changed, starting from their consumption patterns where they prefer to buy food from outside using applications because it is more practical. This causes the amount of plastic waste to increase because the food purchased uses plastic materials. This study aims to analyze the effect of green products and digital marketing both partially and simultaneously on purchasing decisions at Starbucks Cemara Asri. This research is descriptive research with a quantitative approach. The sample in this study amounted to 140 Starbucks consumer respondents with random sampling techniques selected through non-probability sampling with accidental sampling techniques. Data collection was carried out through distributing questionnaires. The collected data were analyzed by multiple linear regression. The results showed that green product and digital marketing had a significant partial and simultaneous effect on purchasing decisions at Starbucks Cemara Asri.